In silico and in vitro assay of Hexagamavunon-6 analogs, Dibenzilyden-N-Methyl-4-piperidone as antibacterial agents - Tesia Aisyah Rahmania, Ritmaleni Ritmaleni, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2020)
A new series of analogs Hexagamavunon-6 (HGV-6) was prepared and screened for antibacterial activity against Streptococcus mutans (ATCC 25175), Escherichia coli (ATCC 25922), Bacillus subtilis (ATCC 6633), Psedomonas aeruginosa (ATCC 27853), Klebsiella pneumoniae, and Enterococcus faecalis (ATCC 29212) using disk diffusion method. The antibacterial results showed that 3,5-Bis-(2',4'-dichlorobenzilyden)-N-methyl-4-piperidone (1c) compound display significant inhibition and broad-spectrum antibacterial activity. This is in accordance with the in silico evaluation showing that compound 1c has a lower docking score than both compounds 1a and 1b. None of the tested compounds were as active as the reference standard drug Amoxicillin.
Keywords: Analog curcumin, Hexagamavunon-6 (HGV-6), dichlorobenzilyden N methyl piperidine, antibacterials activity, disk diffusion